The Effectiveness of Communicative Language Teaching (CLT) Through An Educational CSR Program for Primary School Students: Participants’ Perspective - Mohd Rusdy Yaacob; Norafizah Abas; Sazuan Nazrah Mohd Azam; Aimie Nazmin Azmi; Nurul Ain Mohd Said; Musa Yusup Lada; Aine Izzati Binti Tarmizi; Mohamad Riduwan Bin Md Nawawi; Hidayat Bin Zainuddin; Muliati Binti Sedek; Teh Zanariah Binti Mohd Raus (Penerbit USIM, 2025)
E-Proceedings International Language and Education Innovation Competition 2024 (I-INNOLED 2024) “Navigating The Future of Language And Education In A Transformative Era” 15-16 October 2024 Organized by : Faculty Of Major Language Studies Editors: Lubna Abd. Rahman, Amiliayanti Abd Halim, Maziahtusima Ishak